Disproportionate emission of bubble streams with killer whale biphonic calls: Perspectives on production and function - Bowles, Ann E.; Grebner, Dawn M.; Musser, Whitney B.; Nash, Juliette S.; Crance, Jessica L. (The Journal of the Acoustical Society of America, 2015)
Stereotyped pulsed calls were attributed to 11 killer whales (Orcinus orca) with and without synchronous bubble streams in three datasets collected from two facilities from 1993 to 2012. Calls with and without synchronous bubble streams and divergent overlapping high frequency components (“biphonic” vs “monophonic”) were compared. Subjects produced bubbles significantly more often when calls had divergent high frequency components. However, acoustic features in one biphonic call shared by five subjects provided little evidence for an acoustic effect of synchronous bubble flow. Disproportionate bubbling supported other evidence that biphonic calls form a distinct category, but suggested a function in short-range communication.